OPTIMIZATION OF SWEETENER ISOLATION FROM STEVIA LEAVES USING RESPONSE SURFACE METHODOLOGY (RSM) - Kamila, K; Fachraniah, F; Harunsyah, H (Jurnal Sains dan Teknologi Reaksi, 2025)
The optimization of sweetener isolation from stevia leaves was carried out using the Response Surface Methodology (RSM). This study aimed to optimize the isolation process of sweeteners from Stevia rebaudiana Bertoni through RSM. The independent variables used were the number of extraction cycles (A) and particle size of the material (B), with four response parameters: extract yield percentage, sweetness level (%Brix), calorie content, and sweetness intensity. The experimental design applied the Central Composite Design (CCD) with quadratic regression model analysis. The results showed that both independent variables had significant effects on the response parameters, either individually or through interaction. Finer particle size (60–70 mesh) combined with the optimal number of extraction cycles enhanced sweetness and reduced the calorie content of the extract. The optimum conditions were obtained at 70 mesh particle size and two extraction cycles, with predicted values of 6.93% yield, 5.80% Brix sweetness, 27.02 kcal/100 g calories, and a sweetness intensity of 7.08. Model validation confirmed a good agreement between predicted and actual values, indicating that RSM is effective for optimizing the sweetener isolation process from stevia leaves. Keywords: Extraction, Extraction cycle, Optimization, Particle size, RSM (Response Surface Methodology), Stevia.